The Impact of Globalization on Social Change and Democratization in Indonesia - Mastiwi Putri Harefa; Timbul Dompak; Etika Khairina; Iranda Firiansyah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Both the process of democratization and the societal change that has taken place in Indonesia have been significantly influenced by globalization. The purpose of this study is to conduct a literature review that focuses on the relationship between globalization, social transformation, and the growth of democracy in Indonesia. With the help of a qualitative methodology that is founded on literature studies, this research investigates the ways in which the flow of information, technology, and global values influences the mentalities of individuals, as well as the social structures and political dynamics in Indonesia. The findings of the study indicate that globalization fosters the development of a society that is more receptive to democratic principles, such as the protection of human rights, the freedom of expression, and the provision of opportunities for political engagement. There are, however, challenges that come along with globalization. These challenges include socio-economic inequality, the erosion of local values, and threats to ethnic and cultural sovereignty. With globalization serving as a catalyst in improving political freedom and expanding civil society involvement, the process of democratization in Indonesia developed fast after the reforms that took place in 1998. The findings of this study highlight the significance of policies that are capable of striking a balance between the impact of globalization and the maintenance of local identity. This is necessary in order to bring about social change that is inclusive and to enhance democracy in Indonesia in a way that is sustainable.